Comparison of Hashin and Puck criterions for failure behavior of pin loaded composite plates - Dogan, C.; Kaman, M. O.; Erdem, S.; Albayrak, M. (Wiley-V C H Verlag Gmbh, 2024)
In this study, the failure behavior of carbon fiber-reinforced pin-jointed composite plates were analyzed for different criteria. For this purpose, composite plates with a single and double pin joints were prepared from four layers carbon fiber composites. The effect of pin number, pin position on plate damage load and type was investigated experimentally and numerically under the tensile test. Numerically, progressive damage analysis was performed using Hashin and Puck failure criteria, and the approach rates to the experimental results were determined. It was observed that the experimental results obtained for single pin joint composites and the numerical data obtained using the Puck damage criterion were at least 87 % compatible, and this rate was determined as 85 % for the Hashin failure criterion. For the double pin jointed composites, it was seen that the experimental results and the results of the Puck damage criterion were compatible with at least 90 %, and this rate was obtained as 84 % for the Hashin failure criterion. The dominant damage type seen in the specimen is matrix shear and fiber compression according to the Hashin damage criterion, inter fiber failure in transverse tension for Puck. Two different ways are followed; firstly, in the experimental study: tensile strength of the thin composite plate loaded with pin, secondly, in the numerical study: estimation of mechanical behavior of plates with two different progressive failure analyzes using Hashin and Puck criteria. The load-displacement graph of each specimen was obtained numerically. image
Vergleich der Hashin- und Puck-Kriterien für das Versagensverhalten von stiftbelasteten Verbundwerkstoffplatten
Keywords: hashin; laminated composite; pin joint; progressive failure analysis; Puck; Hashin; laminierter Verbundwerkstoff; progressive Versagensanalyse; Stiftverbindung